An Overview of Unmanned Aerial Vehicles Technologies for Office Use and Services Delivery - Olarewaju T. OGINNI (FUDMA Journal of Engineering and Technology, 2025)
Universities are transforming into smart ecosystems driven (SED) by technology, transforming office logistics from inefficient processes to faster, more efficient, and innovative ones, thereby enhancing modern communication. Quadcopter drones (QCD) with delivery systems are revolutionizing office logistics by increasing efficiency, reducing costs, and boosting productivity. The paper explores the feasibility and functionality of a drone-based system for autonomously transporting small office items, aiming to improve efficiency, reduce human effort, and provide a reliable, secure intra-office delivery method. Unmanned Aerial Vehicles (drones) are transforming office spaces by eliminating human couriers and facilitating document transportation, especially for physical documents like examination scripts, parcels, and administrative files, thereby improving operational efficiency. The overview examines how automated drone delivery systems (ADDS) can be utilized in offices to improve operational efficiency, productivity, and comfort by focusing on pick-and-delivery mechanisms and technologies that offer practical solutions for office deliveries and automation. It examines the functionality of a quadcopter drone for outdoor delivery applications, focusing on delivery mechanisms, classification, aerodynamics, control systems, power management, battery efficiency, area navigation, obstacle avoidance, challenges, payload capacity, case studies, and security measures. The outcomes showed that drones can carry 500 grams to 2 kilograms and navigate university campuses within 2-5 km, transferring documents like transcripts, letters, memos, and USB drives using lightweight folders, envelopes, or hard cases securely fastened in the drone's payload compartment. The implementation of an autonomous quadcopter drone for university document delivery is expected to enhance inter-faculty communication, decrease staff workload, and boost operational efficiency. The review promotes the integration of smart technologies in corporate operations, aiming to enhance the efficiency and innovation of university campuses.
Keywords: Universities, modern communication, smart technologies, delivery system, operational efficiency.